Individual and Regional Factors of Access to the Renal Transplant Waiting List in France in a Cohort of Dialyzed Patients. Issue 4 (10th March 2015) - Bayat, S.; Macher, M. A.; Couchoud, C.; Bayer, F.; Lassalle, M.; Villar, E.; Caillé, Y.; Mercier, S.; Joyeux, V.; Noel, C.; Kessler, M.; Jacquelinet, C.; et al.
Abstract: Several studies have investigated geographical variations in access to renal transplant waiting lists, but none has assessed the impact on these variations of factors at both the patient and geographic levels. The objective of our study was to identify medical and non‐medical factors at both these levels associated with these geographical variations in waiting‐list placement in France. We included all incident patients aged 18–80 years in 11 French regions who started dialysis between January 1, 2006, and December 31, 2008. Both a multilevel Cox model with shared frailty and a competing risks model were used for the analyses. At the patient level, old age, comorbidities, diabetic nephropathy, non‐autonomous first dialysis, and female gender were the major determinants of a lower probability of being waitlisted. At the regional level, the only factor associated with this probability was an increase in the number of patients on the waiting list from 2005 to 2009. This finding supports a slight but significant impact of a regional organ shortage on waitlisting practices. Our findings demonstrate that patients' age has a major impact on waitlisting practices, even for patients with no comorbidity or disability, whose survival would likely be improved by transplantation compared with dialysis. Abstract : This study demonstrates that in addition to individual factors such as age and comorbidities, the accumulation of patients on the waiting list, likely related to regional variations in organ shortage, impacts placement on the renal transplant waiting list in France.